(Re-)inventing our selves/ourselves : identity and community in contemporary South African short fiction cycles. - Marais, Susan Jacqueline (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2014)
In this study I focus on a number of collections of short fiction by the South African writers Joël Matlou, Sindiwe Magona, Zoë Wicomb and Ivan Vladislavić, all of which evince certain of the characteristics of short story cycles or sequences. In other words, they display what Forrest L. Ingram describes as "a double tendency of asserting the individuality of [their] components on the one hand and of highlighting, on the other, the bonds of unity which make the many into a single whole" . The cycle form, thus defined, is characterised by a paradoxical yet productive and frequently unresolved tension between "the individuality of each of the stories and the necessities of the larger unit" , between "the one and the many" , and between cohesion and fragmentation. It is this "dynamic structure of connection and disconnection" which singularly equips the genre to represent the interrelationship of singular and collective identities, or the "coherent multiplicity of community" . Ingram, for example, asserts that "Numerous and varied connective strands draw the co-protagonists of any story cycle into a single community. "¦ However this community may be achieved, it usually can be said to constitute the central character of a cycle" . Not unsurprisingly, then, in its dominant manifestations over much of the twentieth century the short story cycle demonstrated a marked inclination towards regionalism and the depiction of localised enclaves, and this tendency towards "place-based short story cycles" in which topographical unity is a conspicuous feature was as pronounced in South Africa as elsewhere. However, the specific collections which are my concern here increasingly employ innovative and self-reflexive narrative strategies that unsettle generic expectations and interrogate the notions of regionalism and community conventionally associated with the short story cycle. My investigation seeks to explain this shift in emphasis, and its particular significance within the South African context.
Keywords: South African fiction (English) -- History and criticism; Matlou, Joël -- Criticism and interpretation; Magona, Sindiwe -- Criticism and interpretation; Vladislavić, Ivan, 1957- -- Criticism and interpretation; Wicomb, Zoë -- Criticism and interpretation